Review of Major Hydraulic Modeling Results for Feilaixia Proje ct - XU Feng_jun; XIE Yu_feng; ZHOU Pei_ling (Renmin Zhujiang)
This paper summarizes a series of tests and inve stigations on general layout,const ruction diversion,flood disposal,navigation,river closure,form of gate opening s ection,pattern of energy dissipation and scouring under sluice carried out for F eilaixia Proj ect by the Scientific Research Institute of PRWRC during the period from 1983 to 1998 and presents their major results.